Effects of rotor speed on threshing unit losses and power requirement when using different patterns of guide vane inclination of axial flow threshing unit for chainat 1 rice variety - Chuan-udom, Somchai (Asia-Pacific Journal of Science and Technology, 2017)
The objective of this study was to study effects of rotor speed on threshing unit losses and power requirement when using different patterns of guide vane inclination of axial fl ow threshing unit for Chainat 1 rice variety. Results of the study indicated that the increasing of the rotor speed caused the decreasing in threshing unit losses, but the amount of grain breakage and power requirement were increased. However, the rotor speed of 16 to 18 m/s should be used when the losses, the power requirement and the amount of grain breakage were taken into consideration. The guide vane at the inlet and outlet parts should be fi xed at 60 and 70 degree with the axis of the threshing shaft, respectively.